'The main objection to numerous small bee keepers': biosecurity and the professionalization of beekeeping. (January 2020) - Andrews, Eleanor
Abstract: In the mid nineteenth century, advances in apicultural science and new technologies made beekeeping more efficient and profitable, and it rapidly went from being a cottage industry to a commercial one. But the very technologies and practices that revolutionized beekeeping led directly and indirectly to the spread of an infectious honey bee disease called foulbrood. This was true most of all in upstate New York, which for many decades was at the center of the scientific, technological, and commercial advances, as well as the outbreaks of foulbrood. In this article, I draw on USDA publications, articles from trade magazines, personal papers, and other texts from the late nineteenth and early twentieth centuries to show how the institutions that arose to protect and support the industry formed an 'envirotechnical regime' that promoted a particular vision of 'good beekeeping'. The regime characterized foulbrood as manageable only by beekeepers who were 'financially interested' or 'more deeply engaged in the industry'. This set of beekeepers was contrasted with a second class of smaller scale beekeepers, which was framed as 'negligent' and discouraged from continuing to keep bees. This article shows how efforts to professionalize beekeeping were made in the name of biosecurity and contributes to scholarship more broadly on how norms and institutions developed as a part of the modernization of American agriculture. Highlights: New York State was the center of both modern beekeeping and its ills. Modern beekeeping tools and practices inadvertently spread honey bee disease. A new beekeeping regime was built around biosecurity. Beekeeping was specialized and professionalized in the name of biosecurity.